Full transcriptome analysis of early dorsoventral patterning in zebrafish. - Erika Fodor; Áron Zsigmond; Balázs Horváth; János Molnár; István Nagy; Gábor Tóth; Stephen W Wilson; Máté Varga (PLoS ONE)
Understanding the molecular interactions that lead to the establishment of the major body axes during embryogenesis is one of the main goals of developmental biology. Although the past two decades have revolutionized our knowledge about the genetic basis of these patterning processes, the list of genes involved in axis formation is unlikely to be complete. In order to identify new genes involved in the establishment of the dorsoventral (DV) axis during early stages of zebrafish embryonic development, we employed next generation sequencing for full transcriptome analysis of normal embryos and embryos lacking overt DV pattern. A combination of different statistical approaches yielded 41 differentially expressed candidate genes and we confirmed by in situ hybridization the early dorsal expression of 32 genes that are transcribed shortly after the onset of zygotic transcription. Although promoter analysis of the validated genes suggests no general enrichment for the binding sites of early acting transcription factors, most of these genes carry "bivalent" epigenetic histone modifications at the time when zygotic transcription is initiated, suggesting a "poised" transcriptional status. Our results reveal some new candidates of the dorsal gene regulatory network and suggest that a plurality of the earliest upregulated genes on the dorsal side have a role in the modulation of the canonical Wnt pathway.